2008
DOI: 10.1021/jm800154m
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Testing of Non-Nephrotoxic Desazadesferrithiocin Polyether Analogues

Abstract: A series of iron-clearing efficiencies (ICEs), ferrokinetics, and toxicity studies for (S)-2-(2,4-dihydroxyphenyl)-4,5-dihydro-4-methyl-4-thiazolecarboxylic acid (deferitrin, 1), (S)-4,5-dihydro-2-[2-hydroxy-4-(3,6,9-trioxadecyloxy)phenyl]-4-methyl-4-thiazolecarboxylic acid (2) and (S)-4,5-dihydro-2-[2-hydroxy-3-(3,6,9-trioxadecyloxy)phenyl]-4-methyl-4-thiazolecarboxylic acid (3) are reported. The ICEs in rodents are shown to be dose-dependent and saturable for ligands 2 and 3 and superior to 1. Both polyether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(87 citation statements)
references
References 64 publications
(214 reference statements)
2
85
0
Order By: Relevance
“…5 The data in this study suggest that the fraction of the oral dose of FBS0701 not bound to iron is largely excreted renally whereas the drug:iron complex is likely to be excreted predominantly via the biliary route.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…5 The data in this study suggest that the fraction of the oral dose of FBS0701 not bound to iron is largely excreted renally whereas the drug:iron complex is likely to be excreted predominantly via the biliary route.…”
Section: Discussionmentioning
confidence: 72%
“…[2][3][4] FBS0701 was selected for clinical development on the basis of its primary pharmacological and pharmacokinetic properties and the toxicity profile, all of which suggested that FBS0701 might offer significant clinical advantages for patients with iron overload as compared to currently available therapies. 5 Extensive preclinical toxicological studies of FBS0701 consistently demonstrated a higher no-observableadverse-effect level (NOAEL) compared to deferasirox (ExJade ® , Novartis) suggesting a favorable clinical safety profile especially with respect to nephrotoxicity. 6,7 In this study, we report the results of the first multi-dose exposure of FBS0701 in iron-overloaded patients.…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, FBS0701 bound Fe(III) with very high affinity and selectivity and demonstrated a Ͼ 4-fold higher no-observable-adverse-effect level compared with DFX, suggesting a favorable clinical safety profile, especially with respect to gastrointestinal and renal toxicity. 88 Multidose safety and pharmacokinetic studies in iron-overloaded patients established the acute safety of FBS0701 and the feasibility of once-a-day dosing, 89 and a phase 2 study has now been reported confirming these observations. 90 …”
Section: Fbs0701mentioning
confidence: 81%
“…The error bars represent the standard error of the mean. addition, FBS0701 is more efficient at chelating iron in mice and monkeys than is DFO (29,30). Moreover, Ferrer et al (22) showed that FBS0701 can chelate and remove intracellular erythrocytic iron.…”
Section: Discussionmentioning
confidence: 99%